Computer-augmented modeling studies of Pb(II) and Cd(II) complexes with maleic acid in ethylene glycol–water mixture. Issue 1 (1st October 2016) - Nageswara Rao, Ch.; Srinu, Bogi; Gowri Kumari, V.; Sailaja, B. B. V.
Abstract: Chemical speciation of binary complexes of Pb(II) and Cd(II) ions with maleic acid have been studied pH metrically in the concentration range of 0–50% v/v ethylene glycol (EG)–water mixtures maintaining an ionic strength of 0.16 molL −1 at 303 K. Alkalimetric titrations were carried out in different relative concentrations of metal and maleic acid. Stability constants of various models of binary complexes were refined with MINIQUAD75. The best-fit chemical models were selected based on statistical parameters and residual analysis. The species detected are ML2, ML3, and ML2 H for Pb(II) and Cd(II). The chemical speciation, metal bioavailability, and transportation are explained based on the distribution diagrams.